Sexual dimorphism in relationships between of plasma creatinine and some neuro-endocrine parameters - Walery Zukow; Anatoliy Anchev; Xawery Żukow; Igor Popovych (Kazimierz Wielki University, 2022)
Background. Earlier we found that plasma uric acid and urea causes modulating effects on neuro-endocrine parameters, as well as reactive anxiety, but these effects are significantly different in men and women of different ages. The purpose of this study is to analyze the relationships between the plasma creatinine level and some psycho-neuro-endocrine parameters in the same cohort. Materials and Methods. The object of observation were almost healthy volunteers: 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). In basal conditions we determined plasma levels of creatinine and adaptation hormones, estimated the severity of the trait and reactive anxiety, recorded the ongoing HRV and EEG. After 4 or 7 days, repeated testing was performed. Results. By building regression models with stepwise exclusion, it was found that in men plasma creatinine downregulates the level of Cortisol (r=-0,41) while upregulates the levels of Testosterone (r=0,36) and Calcitonin (r=0,30). The degree of determination of endocrine parameters is 31,9%. In postmenopausal women, creatinine also upregulates Testosterone (r=0,43) while downregulates the amplitude and PSD of β-rhythm in different loci as well as causes right lateralization of β-rhythm. The degree of determination of neuro-endocrine parameters is 61,2%. In women of reproductive age creatinine upregulates the PSD of ULF band HRV and α-rhythm in 5 loci as well as the Entropy of EEG in F3 locus while downregulates the Entropy in T6 locus, F3-δ and T6-θ PSD as well as Cortisol level. The degree of determination of neuro-endocrine parameters is 94,0%. Conclusion. Plasma creatinine has a modulating effect on neuro-endocrine parameters, but this effect is significantly different in men and women of different ages.